2008
DOI: 10.4049/jimmunol.181.2.1103
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal Receptor Activator of NF-κB Ligand Controls Langerhans Cells Numbers and Proliferation

Abstract: Langerhans cells (LC) are the dendritic APC population of the epidermis, where they reside for long periods and are self-replicating. The molecular signals underlying these characteristics are unknown. The TNF superfamily member receptor activator of NF-κB ligand (RANKL, TNFSF11) has been shown to sustain viability of blood dendritic cells in addition to its role in promoting proliferation and differentiation of several cell types, notably osteoclasts. In this study, we have studied expression of the RANKL sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 39 publications
(40 citation statements)
references
References 40 publications
(48 reference statements)
4
35
1
Order By: Relevance
“…Using transgenic mice that overexpress CD40L or RANKL in keratinocytes, it has been shown that RANKL suppressed autoimmunity induced by CD40L (42). Interestingly, in this system the numbers of epidermal LCs were greatly reduced by CD40L (43), suggesting that CD40L might regulate LC numbers, as was recently suggested also for RANKL (44). Oral DCs have the capability to express RANK (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Using transgenic mice that overexpress CD40L or RANKL in keratinocytes, it has been shown that RANKL suppressed autoimmunity induced by CD40L (42). Interestingly, in this system the numbers of epidermal LCs were greatly reduced by CD40L (43), suggesting that CD40L might regulate LC numbers, as was recently suggested also for RANKL (44). Oral DCs have the capability to express RANK (Fig.…”
Section: Discussionsupporting
confidence: 59%
“…Also survival of terminally differentiated mo-DCs and CD34-mDCs required NF-kB activity, though the cells could be rescued from inhibitor-induced apoptosis by the simultaneous presence of activation signals. Reduced survival due to decreased NF-kB activity has been described even in the presence of activation stimuli (23,30,46,47), but these discrepancies probably result from differences in species, DC type, or experimental setup. Together, our data clearly show that canonical NF-kB plays a nonredundant role in the regulation of survival of differentiating as well as fully differentiated monocyte-and CD34-derived human myeloid DC.…”
Section: Discussionmentioning
confidence: 99%
“…RANKL has already been found to play an important role in the regulation of numerous dendritic cell (DC) functions, such as enhancement of T-cell activation capacity (1), increased release of proinflammatory cytokines (2) and prolonged cell survival (3,4). Furthermore, RANKL is expressed on inflamed or activated keratinocytes and induces activation of epidermal Langerhans cells (LC) (5). Particularly, RANKL seems to induce LC to regulate peripheral numbers of CD4 + CD25 + regulatory T cells (T reg ) (6).…”
Section: Introductionmentioning
confidence: 99%